Effects of Forskolin on Trefoil factor 1 expression in cultured ventral mesencephalic dopaminergic neurons. (3rd December 2015) - Jensen, P.; Ducray, A.D.; Widmer, H.R.; Meyer, M.
Highlights: Distinct expression of Trefoil factor 1 in midbrain-derived cell cultures. Trefoil factor 1 is expressed in a subpopulation of dopaminergic neurons. Forskolin treatment increases the number of Trefoil factor 1 containing cells. Forskolin affects Trefoil factor 1 expression through different signaling pathways. Abstract: Trefoil factor 1 (TFF1) belongs to a family of secreted peptides that are mainly expressed in the gastrointestinal tract. Notably, TFF1 has been suggested to operate as a neuropeptide, however, its specific cellular expression, regulation and function remain largely unknown. We have previously shown that TFF1 is expressed in developing and adult rat ventral mesencephalic tyrosine hydroxylase-immunoreactive (TH-ir) dopaminergic neurons. Here, we investigated the expression of TFF1 in rat ventral mesencephalic dopaminergic neurons (embryonic day 14) grown in culture for 5, 7 or 10 days in the absence (controls) or presence of either glial cell line-derived neurotrophic factor (GDNF), Forskolin or the combination. No TFF1-ir cells were identified at day 5 and only a few at day 7, whereas TH was markedly expressed at both time points. At day 10, several TFF1-ir cells were detected, and their numbers were significantly increased after the addition of GDNF (2.2-fold) or Forskolin (4.1-fold) compared to controls. Furthermore, the combination of GDNF and Forskolin had an additive effect and increased the number of TFF1-ir cells by 5.6-fold compared to controls. TFF1 expression was restricted to neuronal cells, and the percentage of TH/TFF1 co-expressing cells was increased to the same extent in GDNF and Forskolin-treated cultures (4-fold) as compared to controls. Interestingly, the combination of GDNF and Forskolin resulted in a significantly increased co-expression (8-fold) of TH/TFF1, which could indicate that GDNF and Forskolin targeted different subpopulations of TH/TFF1 neurons. Short-term treatment with Forskolin resulted in an increased number of TFF1-ir cells, and this effect was significantly reduced by the MEK1 inhibitor PD98059 or the protein kinase A (PKA) inhibitor H89, suggesting that Forskolin induced TFF1 expression through diverse signaling pathways. In conclusion, distinct populations of cultured dopaminergic neurons express TFF1, and their numbers can be increased by factors known to influence survival and differentiation of dopaminergic cells.